Kejadian mastitis subklinis pada kambing perah Peranakan Etawa di desa Bangelan kecamatan Wonosari kabupaten Malang - Mardian, Nur Zaini Nanda; Soeharsono, Soeharsono; Harijani, Nenny; Budiarto, Budiarto; Hermadi, Herry Agoes; Wurlina, Wurlina (Ovozoa: Journal of Animal Reproduction, 2020)
Etawa crossbred goat is one species of goat that is raised for milk production. One of the diseases that often occur in dairy livestock is mastitis, in which there is inflammation of the mammary gland. It is common in goat, that mastitis does not show clinical symptoms (subclinical). This research aims to determine the incidence of subclinical mastitis in Etawa crossbred goats in Bangelan village Wonosari district Malang regency. This research involved 25 respondent farms, which are Etawa crossbred dairy goat farms. In this research, subclinical mastitis cases were directly detected using California Mastitis Test (CMT). The results showed that out of 70 samples collected, 41 (58.6%) samples were positive. These CMT positive goats were from 88% of the respondent farms.